Designing remedies for a recalcitrant administration. Issue 4 (1st October 2020) - Mukherjee, Gaurav; Tuovinen, Juha
Abstract: This article concerns remedial design by courts in cases where constitutional rights are jeopardised by a recalcitrant administration. We focus on the recent judgment of the South African Constitutional Court in Bhekindlela Mwelase v Director-General for the Department of Rural Development and Land Reform – in particular its doctrinal innovation in appointing a Special Master to oversee the processing of labour tenant claims by the Department of Rural Affairs and Land Reform. We argue that the case raises both conceptual and practical questions about the relationship between rights and remedies, substantive law, and the separation of powers. We approach these questions after considering the judgment in its socio-political context through a consideration of the factors underlying the granting of the remedy, from both a theoretical and comparative perspective. The paper identifies a set factors that underpinned the Court's decision that will be likely to influence the granting of invasive remedies in future cases. We then apply these factors to the judgment of the Supreme Court of India in the Right to Food Case to better understand the ways they play out in a different jurisdictional context. These factors can provide doctrinal and normative guidance for courts – especially in the so-called Global South – that often operate under conditions of chronic recalcitrance, inattentiveness, inaction, or incompetence of the coordinate branches of government.